(untitled) (Sociologisk Forskning, 2002)
Autopoiesis and steering: a study on disability policy programs In this article Luhmanns autopoiesis theory is discussed in relation to a specific case; namely political programs with regard to inclusion of disabled persons in the labour market and the implementation difficulties that arise. The article does not attempt to explain the increasing amount of disabled persons excluded from the labour market system. It attempts to explain something more fundamental; how inequality in the labour market system can have such a permanent character. The central question is thus: How come that different programs designed to steer towards an increasing integration of disabled people in the labour market system, does not lead to the intended effect? According to autopoiesis theory, real steering can only be self-steering. Even when steering addresses systems in the environment, is it still self-steering because it is directed towards the system’s own environment, that is, as it is internally constructed by the steering system. Disability policy programs with the objective to increase the inclusion in the labour market of disabled persons, are political programs and as such unable to steer the labour market system.